Acyl‐Functionalized Molybdenum Compounds [(η3‐C3H5)(η5‐Cp′)Mo(CO)2]: An Experimental Study Including the X‐ray Structure of a Rare endo Conformer. Issue 34 (30th October 2014) - Schejbal, Jiří; Honzíček, Jan; Vinklárek, Jaromír; Erben, Milan; Růžičková, Zdeňka
Abstract: A series of new acyl‐functionalized molybdenum(II) complexes [(η 3 ‐C3 H5 )(η 5 ‐C5 H4 COR)Mo(CO)2 ] have been successfully synthesized and crystallographically characterized, and the relationship between the reactivity and electronic properties of these organometallic compounds has been studied in detail. The X‐ray analysis revealed [(η 3 ‐C3 H5 )(η 5 ‐C5 H4 COCF3 )Mo(CO)2 ] to exist as a rare endo conformer, the first time that this structure has been observed in the crystal lattice of a [(η 3 ‐C3 H5 )(η 5 ‐Cp′)Mo(CO)2 ] (Cp′ = substituted Cp) complex without any disorder. It has also been demonstrated that the derivatives bearing very strong electron‐withdrawing acyl groups (e.g., ‐CHO, ‐COCF3 ) show different outcomes in the protonation reactions compared with the parent cyclopentadienyl compound or derivatives bearing less electron‐withdrawing groups (e.g., ‐COMe, ‐COPh). This study has also revealed the increased reactivity of the formyl derivative [(η 3 ‐C3 H5 )(η 5 ‐C5 H4 CHO)Mo(CO)2 ] towards aromatic amines. An IR spectroscopic analysis revealed that the aldimine‐functionalized products formed very quickly even under the mild conditions that fulfill the basic rules of click chemistry. Abstract : A series of new acyl‐functionalized molybdenum(II) complexes [(η 3 ‐C3 H5 )(η 5 ‐Cp′)Mo(CO)2 ] (Cp′ = substituted Cp) have been synthesized. X‐ray diffraction analysis of the CF3 CO derivative revealed a rare endo conformer. In addition, it was found that the electronic properties of the acyl substituents have a strong effect on the outcome of protonation reactions.